Dysfunctional peroxisomal lipid metabolisms and their ocular manifestations - Chen, Chuck T.; Shao, Zhuo; Fu, Zhongjie (Frontiers in Cell and Developmental Biology, 2022)
Retina is rich in lipids and dyslipidemia causes retinal dysfunction and eye diseases. In retina, lipids are not only important membrane component in cells and organelles but also fuel substrates for energy production. However, our current knowledge of lipid processing in the retina are very limited. Peroxisomes play a critical role in lipid homeostasis and genetic disorders with peroxisomal dysfunction have different types of ocular complications. In this review, we focus on the role of peroxisomes in lipid metabolism, including degradation and detoxification of very-long-chain fatty acids, branched-chain fatty acids, dicarboxylic acids, reactive oxygen/nitrogen species, glyoxylate, and amino acids, as well as biosynthesis of docosahexaenoic acid, plasmalogen and bile acids. We also discuss the potential contributions of peroxisomal pathways to eye health and summarize the reported cases of ocular symptoms in patients with peroxisomal disorders, corresponding to each disrupted peroxisomal pathway. We also review the cross-talk between peroxisomes and other organelles such as lysosomes, endoplasmic reticulum and mitochondria.